Life cycle option appraisal in retrofit buildings - Tokede, O.; Love, Peter; Ahiaga-Dagbui, D. (Elsevier, 2018)
© 2018 Elsevier B.V. Determining the economic benefits of building asset retrofitting has been a difficult task due to the paucity of reliable data and the inherent limitations of existing life-cycle costing models. For example, most life cycle costing models do not accommodate revocability (i.e. the economic impacts of reversing a decision previously made on a building configuration). Thus, the impact of revocability in the life cycle appraisal of a retrofit building project is assessed in this paper. Using a case-study approach, the economic impact of revocability is appraised using a real-options framework. The flexibility and non-flexibility of life cycle options are evaluated and compared. It is revealed that the cost of revocability may be as high as 27% in retrofit buildings. Flexible options have up to 50% chance of exceeding the performance of non-flexible retrofit options when fabric insulation measures and smart control installations are considered. The incorporation of renewable energy may undermine the performance of flexible options due to their inherent uncertainties in the cost and evolution in the future. There is, however, a need to develop holistic lifecycle option appraisal approaches for scenario feasiblility assessments to optimise the value of retrofit interventions in buildings.